Whey Protein Supplementation Compared to Collagen Increases Blood Nesfatin Concentrations and Decreases Android Fat in Overweight Women: A Randomized Double-Blind Study - Giglio, Bruna M.; Schincaglia, Raquel M.; Silva, Alexandre S. da; Fazani, Ieda C. S.; Monteiro, Paula A. [UNESP]; Mota, Joao F.; Cunha, Juliana P.; Pichard, Claude; Pimentel, Gustavo D. (Mdpi, 2019)
Protein supplements are usually used to control body weight, however, the impact of protein quality on body fat attenuation is unknown. We investigated the effects of isocaloric isoproteic supplementation of either whey protein (WG) or hydrolysed collagen supplementation (CG) on dietary intake, adiposity and biochemical markers in overweight women. Methods: In this randomized double-blind study, 37 women, [mean +/- SE, age 40.6 +/- 1.7 year; BMI (kg/m(2)) 30.9 +/- 0.6], consumed sachets containing 40 g/day of concentrated whey protein (25 g total protein, 2.4 leucine, 1.0 valine, 1.5 isoleucine, n = 17) or 38 g/day of hydrolysed collagen (26 g total protein, 1.02 leucine, 0.91 valine, 0.53 isoleucine, n = 20) in the afternoon snack. The compliance was set at >70% of the total theoretical doses. The dietary intake was evaluated by a 6-day food record questionnaire. At the beginning and after eight weeks of follow-up, body composition was evaluated by using dual-energy X-ray absorptiometry and lipid profile, insulin resistance, C-reactive protein, adiponectin, leptin and nesfastin plasma concentrations were analyzed. Results: Supplements were isocaloric and isoproteic. There were no differences in caloric intake (p = 0.103), protein (p = 0.085), carbohydrate (p = 0.797) and lipids (p = 0.109) intakes. The branched chain amino acids (BCAA) (GC: 1.8 +/- 0.1 g vs. WG: 5.5 +/- 0.3 g, p < 0.001) and leucine intake (CG: 0.1 +/- 0.1 g vs. WG: 2.6 +/- 0.1 g, p < 0.001) were higher in WG compared to CG. BMI increased in the CG (0.2 +/- 1.1 kg/m(2), p = 0.044) but did not change in WG. WG decreased the android fat (-0.1 +/- 0.3 kg, p = 0.031) and increased nesfatin concentrations (4.9 +/- 3.2 ng/mL, p = 0.014) compared to CG. Conclusions: Whey protein supplementation in overweight women increased nesfatin concentrations and could promote increase of resting metabolic rate as part of body composition improvement programs compared to collagen supplementation for 8 weeks. Additionally, our findings suggest that collagen may not be an effective supplement for overweight women who are attempting to alter body composition.
Keywords: obesity; whey protein; collagen; weight loss; leucine; amino acids